Glucosinolate Metabolites and Brain Health: An Updated Review on Their Potential Benefits in Neurodegenerative, Neurodevelopmental, and Psychiatric Disorders - Claudia Muscarà; Agnese Gugliandolo; Emanuela Mazzon; Gabriella Calì (Antioxidants)
Neurodegenerative, neurodevelopmental, and psychiatric disorders, as well as epilepsy, affect millions of people. Due to their impact on patients’ quality of life, they represent a major health issue. Natural compounds are arising as new treatments for these diseases. Particularly, glucosinolates (GLS) are secondary metabolites found in Cruciferae family plants. Their basic structure consists of a glucose unit linked to a thiohydroximate-O-sulfonate group and an aliphatic, aralkyl, or indolyl side chain, depending on their precursor amino acid. Specifically, aliphatic GLS derive from methionine, aromatic ones from phenylalanine, and indolic ones from tryptophan. Myrosinase (thioglucoside glucohydrolase) is the crucial enzyme for GLS degradation, leading to the production of isothiocyanates (ITCs). ITCs attracted considerable scientific interest for their protective effects against various diseases, thanks to their antioxidant, anti-inflammatory, and neuroprotective properties. Here, we collected the latest evidence regarding ITC effects in neurodegenerative, neurodevelopmental, and psychiatric disorders, including preclinical and clinical studies published in the last decade. These studies evidenced ITCs’ neuroprotective effects, exerted mainly through antioxidant and anti-inflammatory mechanisms. Thus, ITCs’ integration, also through the diet, may represent a safe and efficacious strategy to improve health and limit the risk of neurological and psychiatric disorders. However, new large-scale trials are needed to determine their therapeutic potential, particularly for diseases with no clinical evidence.